Cardioprotective Activity of Cassia fistula L. Bark Extract in Isoproterenol-Induced Myocardial Infarction Rat Model. (23rd August 2022) - Kushwah, Ajay Singh; Mittal, Roopal; Kumar, Manish; Kaur, Gurpreet; Goel, Prerna; Sharma, Rahul Kumar; Kabra, Atul; Nainwal, Lalit Mohan
Abstract : Cassia fistula Linn, generally recognized as Indian laburnum, is one of the ancient trees in the Indian subcontinent used for its ornamental and diverse medicinal properties. It is known for its ethnic medicinal uses in inflammatory and infectious pathologies such as antihelmintic, purgative, carminative, antipyretic, expectorant, analgesic, laxative, antiseptic, and antidote against snake poison. The Cassia bark is rich in anthraquinones, flavanols glycosides, and sitosterols, which renders it cardioprotective properties. The existing experiments were designed to assess the potential of Cassia fistula bark against isoproterenol (ISP)-induced cardiotoxicity in rats, which has not been validated yet. The bark was successively extracted with five different solvents, and each extract was subjected to in vitro antioxidant studies. Further acute oral toxicity assays were carried out preceding in vivo myocardial studies. Cardiotoxicity-inducing agent, ISP, was administrated to the rats for two consecutive days (8th and 9th). Based on in vitro studies, the Cassia fistula methanolic extract (CFME) was administered in two doses: CFME-LD (lower dose 250 mg/kg) and CFME-HD (high dose 500 mg/kg) separately. It was found that CFME produced a substantial decrease in lipid peroxidation and an increase in antioxidants in myocardial tissues. CFME abrogated the levels of triglyceride and total cholesterol with a decrease in alanine transaminase (ALT) and aspartate transaminase (AST) activity in serum at both doses. 2, 3, 5-Triphenyltetrazolium chloride (TTC) staining and histopathology also revealed the protective effects of CFME against ISP-induced myocardial infarction. The study showed the significant role of the CFME as a strong antioxidant and cardioprotective action in ISP-induced toxicity.